2017
DOI: 10.4088/jcp.15m10113
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Apathy Independently Predict Incident Frailty and Disability in Community-Dwelling Older Adults

Abstract: Objective Although depressive symptoms are widely recognized as a predictor of functional decline among older adults, little is known about the predictive utility of apathy in this population. We prospectively examined apathy symptoms as predictors of incident slow gait, frailty and disability among non-demented, community-dwelling older adults. Methods We examined two independent prospective cohort studies - the LonGenity study (N = 625, 53% women, mean age 75.2 years) and the Central Control of Mobility in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 74 publications
4
57
4
Order By: Relevance
“…This risk increases with the increase in apathy. This relationship was independent of depressive symptoms even after taking into account demographic factors, health status and cognitive functioning (Ayers et al, 2017).…”
Section: Depressive Symptomsmentioning
confidence: 81%
See 1 more Smart Citation
“…This risk increases with the increase in apathy. This relationship was independent of depressive symptoms even after taking into account demographic factors, health status and cognitive functioning (Ayers et al, 2017).…”
Section: Depressive Symptomsmentioning
confidence: 81%
“…Since depression is a psychiatric determinant of FS, one should also mention the other relevant neuropsychiatric symptoms of apathy common in the elderly population. Apathy symptoms more likely result from damage to the fronto-subcortical pathways that manifest in declining cognitive, emotional, and motoric goal-directed behavior (Ayers et al, 2017). Although apathy in displayed symptoms resembles depression, clinically this other pronounced psychiatric condition that can occur in the absence of depression and apathy pose a certain diagnostic challenge.…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…4 Some authors have found a significant association between depression and disability. 5,6 Cognitive dysfunction represents a distinct biological and clinical dimension in MDD. It is well known that cognitive performance strongly affects psychosocial functioning and, particularly, working ability in patients diagnosed with MDD 7 as well as with bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence was 21.6% among the 777 individuals (mean age 76.5 years) receiving outpatient care for a chronic disease. 12 As for the prevalence of frailty in nursing homes, a review of the literature by Kojima showed that as many as 46…”
Section: Explanationmentioning
confidence: 99%
“…As for the psychological risk factors, a review by Vaughan et al 45 highlighted the significance of depression, and a review by Ayers et al found apathy to be another risk factor. 46 Monin et al reported a partner effect whereby an individual's frailty predicted the spouse's frailty. 47 Other physical factors reported to be significantly associated with incident frailty include hearing impairment, 48 chronic widespread pain 49 and polypharmacy 50,51 (see CQ37).…”
Section: Explanationmentioning
confidence: 99%